New Focus on Retrospective Methods. Resuming Methodological Dis-cussions: Case Studies from Northern Europe. Edited by Eldar Heide & Karen Bek-Petersen. - Guðmundsdóttir, Aðalheiður (Collegium Medievale, 2016)
The present anthology is rooted in collaboration that began at the 14th International Saga Conference in Uppsala in 2009, where Eldar Heide discussed the need for greater methodological awareness in studies dealing with the use of post-medieval material in the study of Old Norse religion and mythology, and also of Old Norse literature and history. This was then followed up by the founding of the Retrospective Methods Network, which started by promoting a conference the following year in cooperation with the Centre for Medieval Studies at the University of Bergen and has been active since. New Focus on Retrospective Methods is a collection of articles that were originally presented as papers at the conference.